Interferon-induced Sus scrofa Mx1 blocks endocytic traffic of incoming influenza A virus particles - Palm, Mélanie (EDP Sciences, 2010)
The interferon-induced Mx proteins of vertebrates are dynamin-like GTPases, some isoforms of which can additionally inhibit the life cycle of certain RNA viruses. Here we show that the porcine Mx1 protein (poMx1) inhibits replication of influenza A virus and we attempt to identify the step at which the viral life cycle is blocked. In infected cells expressing poMx1, the level of transcripts encoding the viral nucleoprotein is significantly lower than normal, even when secondary transcription is prevented by exposure to cycloheximide. This reveals that a pretranscriptional block participates to the anti-influenza activity. Binding and internalization of incoming virus particles are normal in the presence of poMx1 but centripetal traffic to the late endosomes is interrupted. Surprisingly but decisively, poMx1 significantly alters binding of early endosome autoantigen 1 to early endosomes and/or early endosome size and spatial distribution. This is compatible with impairment of traffic of the endocytic vesicles to the late endosomes.